2013
DOI: 10.2149/tmh.2013-09
|View full text |Cite
|
Sign up to set email alerts
|

A High Incidence of Intussusception Revealed by a Retrospective Hospital-Based Study in Nha Trang, Vietnam between 2009 and 2011

Abstract: Rotavirus is a leading cause of severe diarrhea among children worldwide. Thus, the World Health Organization recommended including rotavirus vaccines in national immunization programs. One concern about rotavirus vaccine, however, is a possible association with intussusception. Thus, it is crucial to know the baseline incidence of intussusception in the first year of life. A study conducted in Hanoi, Vietnam showed that the incidence of intussusception was the highest in the world. This retrospective cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…We observed only few cases during the first three months of life. This finding is consistent with earlier studies in Bangladesh [18] and Vietnam [19] which also reported either very few cases or no cases at all during the first 3 months of age. This finding is crucial from a programmatic point of view.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed only few cases during the first three months of life. This finding is consistent with earlier studies in Bangladesh [18] and Vietnam [19] which also reported either very few cases or no cases at all during the first 3 months of age. This finding is crucial from a programmatic point of view.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, they found increasing trend of intussusception with a peak at 11 and 12 months of age following by a persistent higher number of cases till 23 months of age and then a gradual decline until 3 years of life and beyond. The study in Vietnam also observed higher number of intussusception even after 2 years of age [19].…”
Section: Discussionmentioning
confidence: 99%
“…[12] In spite of such dire consequences, possibility of spontaneous reduction of SBIs should be considered. [16,24,25] Of the 81 patients in the present study, 17 had SBI (15 IL, 2 JJ) that reduced spontaneously.…”
Section: Discussionmentioning
confidence: 65%
“…The authors also noted the potential mistake of recording surgically treated intussusception cases in diagnosis databases with codes for gastrointestinal diseases rarely associated with intussusceptions or for potential complications of intussusception, such as "intestinal obstruction." [16] While the majority (51 cases, 63%) were diagnosed at least 24 hours after onset of the symptoms, 23.5% of cases required surgery. Of the 19 patients who underwent surgery, only 4 (4.9% of the total patient population) required resection of necrotic intussuscepted intestinal segments.…”
Section: Discussionmentioning
confidence: 98%
“…In the US and Europe, there is a low level risk of intussusception with the current licensed rotavirus vaccines, Rotarix® and RotaTeq®. The incidence of intussusception, which occurs naturally in infants, begins to increase at 2–3 months of age and peaks at 4–8 months of age [18] , coinciding with the administration of rotavirus vaccines. Thus, temporal associations with vaccines are not necessarily causal.…”
Section: Proceedings Of Meetingmentioning
confidence: 99%